PENGARUH CITRA MEREK, KEPERCAYAAN, DAN KOMITMEN TERHADAP LOYALITAS PELANGGAN APLIKASI TRANSPORTASI ONLINE GOJEK DI KOTA MALANG - M. Afif Fathi Ramadhan (Jurnal Ilmu Manajemen (JIMMU), 2020)
This study aims to determine the effect of brand image on trust, brand image on loyalty, brand image on commitment, trust and commitment to loyalty, and indirect influence of brand image on loyalty mediated trust, and indirect influence of brand image on loyalty mediated commitment. The population in this study is unknown. Sampling in this study using incidental sampling and purposive sampling techniques as many as 96 respondents. The analysis is done using path analysis. The results of this study indicate that brand image has a positive and significant effect on trust, brand image has a positive and significant effect on loyalty, brand image has a positive and significant effect on commitment, trust and commitment has a positive and significant effect on loyalty, there is an indirect effect of brand image on loyalty through trust, there is an indirect influence of brand image on loyalty through commitment.Keywords: Brand Image, Trust, Commitment, Loyalty.